Association between Helicobacter pylori Infection and Nonalcoholic Fatty Liver Disease: A Single-Center Clinical Study - Ou Cai; Zhenpeng Huang; Ming Li; Chaoqun Zhang; Fengbo Xi; Shiyun Tan (Gastroenterology Research and Practice)
Objective. To investigate the association between Helicobacter pylori (H. pylori) infection and nonalcoholic fatty liver disease (NAFLD). Methods. Data from 2051 participants who underwent 13C urea breath test and abdominal ultrasound examinations was collected. Participants were allocated to NAFLD risk group and NAFLD nonrisk group based on definite risk factors for NAFLD. The relationship between H. pylori infection and NAFLD was analyzed. Results. No significant difference was found between rates of H. pylori infection and NAFLD using the chi-square test (P=0.30) or regression analysis (P=0.70). There was no significant difference between rates of H. pylori infection with and without NAFLD (P=0.47) in the NAFLD risk group or in the NAFLD nonrisk group (P=0.59). There was no significant difference between rates of H. pylori infection in men (P=0.69) and in women (P=0.27) or in participants aged 18–40 years (P=0.43), 41–65 years (P=0.14), and ≥66 years (P=0.66) with and without NAFLD in the NAFLD risk group or between the same sex or age groups (P=0.82, P=0.66, P=0.24, P=0.53, and P=1.00, resp.) in the NAFLD nonrisk group. Conclusions. H. pylori infection does not appear to increase the NAFLD prevalence rate or to be associated with, or a risk factor for, NAFLD.